TAMIS with partial excision of mesorectum and primary closure of rectal wound using vloc - Alves Filho,Eduardo Fonseca (2015)
Background: Transanal Minimally Invasive Surgery has proven to be a viable alternative in the treatment of rectal tumors; however, rectal wound closure can be challenging. We describe our experience with this procedure using the vloc suture device. Resume: Eight successful Transanal Minimally Invasive Surgery with primary wound closure using vloc were performed in 5 men, 62 years mean age; all cases had pre-operative diagnosis of adenoma with high-grade dysplasia. The surgical anatomic-pathologic results showed 6 adenomas with high-grade dysplasia and 2 well differentiated adenocarcinomas, limited to the upper third of the submucosa (pT1SM1) without lymphatic or vascular invasion. All lesions were resected with negative margins. No patient reported during follow-up rectal pain, fecal incontinence or bleeding. Conclusion: The use of vloc in rectal wound closure during Transanal Minimally Invasive Surgery is secure and facilitates the procedure.